Income mobility: a characterization in Argentina using archetypes - Garrido, Nicolás; Marina, Adriana (Estudios de Economía, 2016)
The aim of this note is to analyze some characteristics about the income mobility problem present in Argentina during the last decade of the last century. In order to reach this goal we propose the concept of archetypes to identify an average economic agent in pseudo-data panel. This identification lets us follow the archetypes through the time and using stochastic kernels we study the dynamic distribution of three archetypes classes: Demographics, Sectors and Human Capital. The main result of this empiric analyzes shows that the Human Capital archetype exhibits the lowest mobility.